2016
DOI: 10.1177/0093650216644023
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Control and Support Mechanisms in Members’ Sense of Virtual Community

Abstract: Research on online communities has emphasized the individual benefits of social support for members, but less is known about how such communities are regulated through organizing processes of support and control. Drawing on a survey of 214 members of a particular online message board community, we develop and test a model of social support, strength of ties, normative influence, and concertive control and their influence on members’ sense of virtual community (SOVC). We find that all four factors predict SOVC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 89 publications
0
40
0
1
Order By: Relevance
“…A particular way of enforcing these norms in a neighborhood context is by withholding aforementioned prosocial neighborly behaviors from neighborhood residents that are not perceived as neighbors or as individuals that do not reciprocate neighborly behaviors (Kusenbach, 2006). Similarly, in online communities, users are sanctioned or banned by group administrators when explicit or tacit norms are violated (Gibbs et al, 2019).…”
Section: Resource Exchange Bridging Behavior and Network Closurementioning
confidence: 99%
“…A particular way of enforcing these norms in a neighborhood context is by withholding aforementioned prosocial neighborly behaviors from neighborhood residents that are not perceived as neighbors or as individuals that do not reciprocate neighborly behaviors (Kusenbach, 2006). Similarly, in online communities, users are sanctioned or banned by group administrators when explicit or tacit norms are violated (Gibbs et al, 2019).…”
Section: Resource Exchange Bridging Behavior and Network Closurementioning
confidence: 99%
“…Previous studies have shown that a strong sense of virtual community can promote the occurrence of user behaviors. For example, Talo [18] believed that a sense of virtual community is positively correlated with community participation behaviors, and users' sense of virtual community can promote the participation of members [19] . Therefore, the following assumptions are made: H3: Users' sense of virtual community is positively correlated with their knowledge contribution.…”
Section: Virtual Community Sensementioning
confidence: 99%
“…The ability to grow OC membership by attracting and retaining members has been used as evidence of the success of online communities (Ma & Agarwal, 2007). Indeed, many OCs suffer from the lack of member attachment and contribution because the relationships formed and the social ties that bind members together may be weaker than in face-to-face communities (Gibbs, Kim & Ki, 2016). When OCs fail to attract new members and when their existing members do not have a strong identification with the OC, they become inactive and therefore fail (Boyd & Ellison, 2007;Phang, Kankanhalli & Sabherwal, 2009;Ma & Agarwal, 2007).…”
Section: From Self-organized Ocs To Founder-led Ocsmentioning
confidence: 99%
“…These communities of often large connectives of dispersed and voluntary members provide opportunities for innovative product designs, knowledge creation, collaboration and learning (Faraj, Kudaravalli & Wasko, 2015;Kane, Johnson & Majchrzak, 2014). However, in contrast to the self-organized, bottom-up OCs, such as support communities (e.g., Phang, Kankanhalli & Sabherwal, 2009;Gibbs, Kim and Ki, 2016) and those that are formed spontaneously as a response to emergencies and natural disasters (e.g., Nan & Lu, 2014;Majchrzak & More, 2011), founderled OCs experience different dynamics, as their survival and growth lie heavily with those who install the foundations for their development, the founders.…”
Section: Introductionmentioning
confidence: 99%